Galdós : The Mature Thought - Dendle, Brian J., 1936- (Book collections on Project MUSE., 1980)
The sheer volume of prolific Spanish novelist and playwright Benito Perez Galdós's literary production has rendered overall assessment of his body of work all but impossible. The later volumes in his ambitious and popular Episodios nacionales series, in particular, have suffered from scholarly indifference. In this acclaimed study, Brian J. Dendle closely considers the twenty-six novels in this series written between 1898 and 1912. These episodios, Dendle contests, are artistically superior to the earlier volumes and offer a unique opportunity to establish the ideological profile of the matur.